Koncepcje kontrolingu przedsiębiorstwa w warunkach globalizacji - Bieńkowska, Agnieszka; Kral, Zygmunt; Zabłocka-Kluczka, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The essence of globalization was presented - peculiar occurrence in a present stage of society and enterprises development. Complexity of the enterprise management in conditions of globalization was pointed and controlling as an instrument that supports management was proposed. The most justifiable controlling concepts of an enterprise in terms of globalization were mentioned. They were discussed taking circumstances caused by globalization into consideration. Their usefulness in specific conditions of enterprises activity was accentuated. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 244-252